Ministry of Finance Decree No. 549 of the year 2010 Concerning The Amendment Of Certain Provisions Of The Executive Regulations Of The Law Regulating Tenders And Bids Promulgated By The Minister Of Finance Decree No. 1367 Of The Year 1998 = وزراة المالية قرار رقم 549 لسنة 2010 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم المناقصات والمزايدات الصادرة بقرار وزير المالية رقم 1367 لسنة 1998 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.